Bingkai Berita Pencegahan Penyebaran Virus Covid-19 pada Kompas.com dan Detik.com - Aris Sumartono; Ahmad Toni (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2021)
The spread of the Corona or Covid-19 virus has spread globally or worldwide, including spread in Indonesia. The spread of this virus is very panic and also causes public unrest. Public anxiety and panic have become excessive with the confusing news regarding Covid-19 so that the truth of the news conveyed becomes a question. In this case, the contribution of mass media or online media is very necessary in delivering messages to the public so that there are no misunderstandings in receiving a message or news. In delivering news, a media must have its own characteristics in constructing the news. The characteristic of this news can be seen from the style of writing news that is conveyed by framing news, commonly known as news framing techniques. The purpose of this research is to get an overview and analyze the understanding of online mass media, namely www.detik.com and Www.kompas.com online in framing the news about preventing the spread of Covid-19 online. Selection of www.detik.com and www.kompas.com with the consideration of being the most popular news portals today. The framing analysis in this study uses the framing model proposed by Robert N. Entman. The results of this study indicate that there are differences in framing news between www.detik.com and www.kompas.com, namely in news delivery. In construction, www.detik.com implements objectivation constructs with a more general or global narrative. While www.kompas.com frames its news by applying an externalized construction where the narrative of the news contains the day's outpouring or the reader's expression, besides that the delivery of news is more detailed and concrete.